Earth reinforcement and soil structures - Jones, Colin J. F. P. (Thomas Telford, 1996)
This volume provides a comprehensive explanation and illustration of earth reinforcement and soil structures, from the viewpoint of practising engineers involved in design and construction. This edition has been updated to reflect the latest changes in theory, materials and practice.